Implementation of the Independent Curriculum at State Senior High School 2 Palembang: Towards a Multitalented Generation - Syaifullah, M. Farhan; Safitri, Putri Dia; Mandasari, Mandasari; Aulia, Putri Miftah; Abdurramansyah, Abdurramansyah (Journal of English Language and Education, 2025)
This study explores the implementation of the Independent Curriculum at SMA Negeri 2 Palembang, aiming to analyze its impact on student-centered learning and character development. Employing a qualitative case study approach, the research involved the entire school community, with purposive sampling of key informants such as the principal, curriculum coordinators, teachers, and students. Data were collected through participatory observation, in-depth interviews, and documentation, and were then analyzed thematically using Miles and Huberman's model. The findings reveal that the school has successfully applied various strategies, including forming a Learning Committee, conducting House Training, and integrating the Pancasila Student Profile Project. These efforts have enhanced student creativity, independence, and skills, although challenges remain in teacher adaptation and resource availability. The study concludes that the Independent Curriculum strengthens student competencies and character, but recommends further comparative research and improved teacher training for broader impact.